SOCIAL INTERACTION OF CIPINANG RESIDENTS TOWARDS THE LGBTQ PHENOMENON: A SOCIAL JUDGMENT PERSPECTIVE BY MUZAFER SHERIF - Humaini; Dias Miranty, Azzahra; Haspiani, Nur Hasanah (Journal of Social Political Sciences, 2025)
This study aims to describe the social interactions of Cipinang residents with the Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ) phenomenon through the lens of Muzafer Sherif's Social Judgment Theory. The study particularly emphasizes two key aspects of Sherif’s theory: Ego Involvement and Attitude. Using a qualitative-descriptive approach with a phenomenological perspective, this research explores how the LGBTQ phenomenon is perceived and responded to by the community. The results show that Cipinang residents exhibit varying responses based on Ego Involvement, with individuals either supporting or opposing the phenomenon. The analysis reveals that while some residents adopt a neutral or accepting attitude towards the LGBTQ phenomenon, considering it a non-issue, others show strong disapproval, actively rejecting its presence in the community. The findings underscore the influence of Attitude in shaping these interactions, where residents’ personal beliefs and cultural values significantly impact their perceptions of the LGBTQ community. These responses highlight the ongoing tension between social acceptance and rejection, shaped by cognitive and emotional investments in societal norms and values